A European Military Balance Organization and Dynamic Conventional Arms Control - William LIPPERT, Ph.D Candidate (Bulletin of "Carol I" National Defense University, 2023)
The Russo-Ukraine War has capped the decay of conventional arms control (CAC) agreements and security institutions designed and evolved in large part to prevent this type of conflict. At its root is the rivalry between Russia and NATO, and Russian concerns over the military balance. The Conventional Armed Forces in Europe (CFE) Treaty was the cornerstone agreement to stabilize the military balance, but the treaty and other security institutions such as the Organization for Security and Cooperation in Europe (OSCE) failed to adapt to NATO expansion. This article explores the role of various organizations in Europe in CAC and proposes a unique approach to future CAC agreements, dynamic CAC, implemented by a dedicated organization called the European Military Balance Organization (EMBO) which would continuously assess the military balance between NATO and Russia.